2017
DOI: 10.1111/ijcs.12371
|View full text |Cite
|
Sign up to set email alerts
|

Gender, generation and sustainable consumption: Exploring the behaviour of consumers from Izmir, Turkey

Abstract: This study investigates the relationship between consumers' sustainable consumption behaviour and both gender and generation-related individual differences in a sample of Turkish consumers. A total of 393 participants from different generations and gender took part in the study. To measure sustainable consumption behaviour, we used four-dimensional sustainable consumption behaviour scale. The results showed that generation is associated with unneeded consumption as a dimension of sustainable consumption behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
81
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 28 publications
4
81
2
Order By: Relevance
“…Wang further noted variations for countries along income levels for environmental governance being driver of sustainable consumption behaviour. Taken together, both Bulut et al (2017) and Wang confirmed that there are country-based differences on what motivates sustainable consumption at individual level. In the remaining section of this literature review, we explore the drivers of sustainable consumption and develop conceptual hypotheses.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 70%
See 3 more Smart Citations
“…Wang further noted variations for countries along income levels for environmental governance being driver of sustainable consumption behaviour. Taken together, both Bulut et al (2017) and Wang confirmed that there are country-based differences on what motivates sustainable consumption at individual level. In the remaining section of this literature review, we explore the drivers of sustainable consumption and develop conceptual hypotheses.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 70%
“…Studies and reports on drivers of sustainable consumption have been country-specific with contradictory results (Bulut et al, 2017;Wang, 2016;Young et al, 2010;Zeegers and Clark, 2014). Therefore, there are no universally acceptable drivers of sustainable consumption.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly true in the consumption field, though consumer choices are also influenced by income level, social status and biases, however, gender is still a significant driver (OECD, 2008;Schultz and Stieß, 2009). Women tend to have less resource-intensive (and therefore more sustainable) lifestyles and display more pro-environmental attitudes, whether rich or poor, while men's consumption patterns and ecological footprint are usually greater than women's (Bulut et al, 2017;Chant, 2006;OECD, 2008). In addition, the gendering of non-sex-differentiated products and services is a standard marketing tool used to assign gender characteristics and increase demand and consumption for given products (UNEP, 2016).…”
Section: Introductionmentioning
confidence: 99%